2016
DOI: 10.1016/j.trf.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Who, where, when: the demographic and geographic distribution of bicycle crashes in West Yorkshire

Abstract: Factors associated with cycle safety, including international differences in injury and mortality rates, protective equipment and bicycle training, have been subject to increasing academic interest. Environmental variables associated with cycle safety have also been scrutinised, but few studies have focussed on geographical factors at the local level. This paper addresses this research gap by analysing a geo-referenced dataset of road traffic incidents, taken from the UK's STATS19 dataset (2005 -2012). We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…Seasonally, while many such deaths occurred in the evening during winter, autumn and spring, a relatively large number also occur during summer mornings and evenings (NRTAC, 1995). In the UK, Lovelace, Roberts, and Kellar (2016) indicated slightly different pattern of accidents for cycling (happen during the daylight, for both cyclists and non-cyclists) but they concentrate during the summer. According to EC (2011) figures for Poland, Hungary and Estonia showed that a large portion of accidents with pedestrians happen in darkness, most certainly because these countries have relatively long winters, with short daylight hours.…”
Section: Temporal Patternsmentioning
confidence: 92%
“…Seasonally, while many such deaths occurred in the evening during winter, autumn and spring, a relatively large number also occur during summer mornings and evenings (NRTAC, 1995). In the UK, Lovelace, Roberts, and Kellar (2016) indicated slightly different pattern of accidents for cycling (happen during the daylight, for both cyclists and non-cyclists) but they concentrate during the summer. According to EC (2011) figures for Poland, Hungary and Estonia showed that a large portion of accidents with pedestrians happen in darkness, most certainly because these countries have relatively long winters, with short daylight hours.…”
Section: Temporal Patternsmentioning
confidence: 92%
“…Cultural and symbolic factors (e.g., Aldred and Jungnickel 2014; Lourontzi and Petachti 2017) affect the variability of mobility choices across and within countries in critical ways (e.g., Jensen 2009;Murtagh, Gatersleben, and Uzzel 2012). Various authors agree that it would be of paramount importance for planners to understand the social and cultural differences in how bicycles are perceived because: they are closely related to differences in people's needs and preferences (e.g., B€ orjesson and Eliasson 2012; Lusk 2019; Lusk, Ferreira da Silva Filho, and Dobbert 2018); and they may have important implications for an individual's choice of mobility style (e.g., Daley and Rissel 2011), as well as for the related safety and security issues (e.g., Alveano-Aguerrebere et al 2017;Lovelace, Roberts, and Kellar 2016).…”
Section: Cultural and Symbolic Factorsmentioning
confidence: 99%
“…Bu kazalara neden olan modern trafik sisteminin problemlerinden biri, trafik sisteminin araba kullanıcısı perspektifinden tasarımlanmış olmasıdır (Wegman ve ark., 2012). Bundan dolayı literatürde trafikte hâkim bir alana sahip arabaların, bisikletliler ile karıştığı kazalar ve çarpışmalar önemli yer tutmaktadır (Lacherez, Wood, Marszalek ve King, 2013;Lovelace, Roberts ve Kellar, 2016;Rasanen ve Summala, 1998). Özellikle bisikletlilerin yaşadığı akan trafikte bisikletlinin algılanmasıyla ilgili problemler, araba ve bisiklet kazalarının temelini oluşturmaktadır.…”
Section: Türkiye'deki Bisiklet Kullanıcılarının Trafikte Görünürlükleunclassified